FORMALIZATION OF REVERSE LOGISTICS PROGRAMS: A THEORETICAL FRAMEWORK - Han, Hui; Cueto, Eva Ponce (Brazilian Journal of Operations & Production Management, 2016)
Formalization would enable firms to profitably handle their reverse logistics operations, especially when returns involve a number of uncertainties such as increasing volume of returns, the unstable time, and different types/conditions of returned products. The main goal of this paper is to propose a theoretical framework that helps firms to implement a formalization program to manage their returns. The framework proposed covers all the stages in reverse logistics process, from return collection to sorting and treatment processes. This research work proposes the theoretical framework that provides instructions for firms formalization, with written rules and standard procedures, to better control their reverse logistics process. Companies can effectively structure their reverse logistics activities with own formalization system based on the theoretical framework proposed in this paper.